Assimilation Of Business Intelligence (BI) And Big Data Analytics (BDA) Towards Establishing Organizational Strategic Performance Management Diagnostics Framework: A Case Study - Jayakrishnan, Mailasan; Mohamad, Abdul Karim; Mohd Yusof, Mokhtar (Digital Information Research Foundation, 2018)
In this research paper, we had observed and proposed the characteristic of Big Data Analytics (BDA) and Business Intelligence (BI) in observing the voluminous picture of organizational strategic performance management diagnostics framework. In our study, we are interested in handling BDA and BI as a dynamic research that had enabled organizations to invade and generate greater knowledge formation and decision-making. Our research goal is to advance a real world understanding of emerging knowledge derived from organizing big data scenarios and BI framework development. In order, to overcome the ambiguity scenarios of BDA, we propose a framework that involve the present BDA and BI stages with their analytic features in designing the organizational strategic performance management framework. The outcome will be a design of a typical strategic performance management application – the organizational strategic diagnostic dashboard.